Research on the design of airport intelligent distribution robot based on Internet of Things technology - Lv Ming; Zhang Rui; Sun Dalin (ITM Web of Conferences)
Under the influence of the current intelligent interaction and Internet of Things environment, service quality is becoming more and more important. The airport is a representative occasion under the service design concept and one of the representative demonstrations in service design. This article focuses on the pain points of passengers carrying luggage and walking for a long time, based on the airport business model and service needs, and proposes a practical design method that combines the Internet of Things and sensing technology in the early design and planning stages. The design of the airport's intelligent delivery robot carries many practical functions such as "large storage space, smart screen, transportation, transportation, and navigation" to provide passengers with the best travel experience. Users can scan the QR code on the APP to rent and enjoy the systematic services provided by intelligent robots. Provide temporary services to passengers after airport security check and before boarding, so as to reduce passenger fatigue and improve passengers' first experience before boarding. Strong service can significantly increase passenger flow and reduce the airport's human resource costs, thereby solving the current pain points. , to achieve a win-win situation for the airport and consumers.